PENGARUH PENDIDIKAN KESEHATAN DENGAN MENGGUNAKAN MEDIA AUDIOVISUAL TERHADAP PENGETAHUAN DAN SIKAP REMAJA MENGENAI UPAYA PENCEGAHAN PENYAKIT MENULAR SEKSUAL - Eka Dwi Yanti; Yulia Irvani Dewi; Sofiana ' Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Sexually Transmitted Disease (STD) is a part of reproduction track infection caused by sexual intercourse, therefore need to be given health education like audiovisual media.  The aim of this study was to know the effect of health education with audiovisual media for adolescent knowledge and attitude about prevent sexually transmitted disease. Design of this study was quasy experiment with non-equivalent with control group design. Sample of this research were 86 respondents which divided into 43 respondents as an experimental group and 43 respondents as a control group based on inclusions criteria using proportional sampling with probability sampling technique. Experimental group was given health education using audiovisual media within 25 minutes of duration. Knowledge and attitude of adolescent was measured by knowledge and attitude about prevent STD questionnaire. Univariate analysis and bivariate analysis was measured by dependent sample T-test and independent sample T-Test. Bivariate analysis showed knowledge p value (0,000) and attitude p value (0,000), which means that health education using audiovisual media was effective for adolescent knowledge and attitude about prevent STD.This research was recommended for the school to applied this media as one of the media learning and for community nurses can increase their knowledge and attitude of teens about the prevention of STD with audiovisual media.   Keywords: Adolescent, attitude, education, knowledge, sexually transmitted disease.